On a class of elliptic systems involving the p(x)-Laplacian and nonlinear boundary conditions - Rasouli, S. H.; K. Fallah (Հայաստանի ԳԱԱ)
In this paper we study an elliptic systems involving the p(x)-Laplacian and nonlinear boundary conditions.
Keywords: Mathematics; Science